BIOHAZ scientific opinion on the equivalence of an alternative heat treatment process of feathers and down - EFSA Panel on Biological Hazards (BIOHAZ); Ana Allende; Avelino Alvarez‐Ordóñez; Valeria Bortolaia; Sara Bover‐Cid; Wietske Dohmen; Laurent Guillier; Lieve Herman; Liesbeth Jacxsens; Lapo Mughini‐Gras; Maarten Nauta; Jakob Ottoson; et al. (EFSA Journal)
Abstract The European Commission requested EFSA to provide a scientific opinion on the equivalence between the heat treatment process of feathers and down with dry heat to a temperature of 100°C for 30 min and the treatment set up in Commission Regulation (EU) No 142/2011, in terms of inactivation of relevant pathogens. To be considered at least equivalent to the methods in the legislation, the alternative method should be able to reduce the concentration of Enterococcus faecalis or Salmonella Senftenberg by at least 5 log10 and the infectious titre of Anelloviridae and Circoviridae by at least 3 log10. An extensive literature search (ELS) was conducted to identify studies in which the log10 reduction or the D value of the indicators were determined after dry heating in matrices with low moisture/water activity. The ELS did not provide any study on the inactivation of E. faecalis by dry heating. For S. Senftenberg, there was no clear data demonstrating a 5 log10 reduction. For Anelloviridae and Circoviridae there was limited evidence and only one study reported 1 log10 reduction after 30 min at 120°C. Given the available data and sources of uncertainty, it is not possible to conclude on a 5 log10 reduction of E. faecalis using the proposed method due to lack of evidence. Similarly, a comparable reduction of S. Senftenberg cannot be concluded due to conflicting evidence. For Anelloviridae and Circoviridae, it was not possible to conclude that a 3 log10 reduction is achieved with the proposed method, as only one study on dry heat was retrieved, which did not demonstrate such a reduction. Therefore, based on data available to date, applying dry heat to feathers and down at 100°C for 30 min cannot be considered equivalent to the treatment specified in the Regulation, in terms of inactivation of relevant pathogens.